Determinan beban pengasuh pasien stroke pasca perawatan di rumah sakit di RSUD dr. Soediran Mangun Sumarso, Wonogiri - Sri Nurjannah; Setyopranoto Setyopranoto (Berita Kedokteran Masyarakat (BKM), 2018)
Determinants caregiver burden of stroke patients after hospitalization in dr. Soediran Mangun Sumarso Hospital, Wonogiri  PurposeThe purpose of this study was to explore the  factors associated with caregiver burden on primary caregivers of stroke patients after treatment in dr. Mangun Soediran Sumarso Wonogiri hospital.MethodObservational research used cross-sectional study approach. The study was conducted in Wonogiri district involving 206 caregivers of stroke patients. Subjects were taken consecutively from those who met the eligibility criteria. Measurement of caregiver burden used Zarit Burden Interview (ZBI). Analysis used Poisson Regression.ResultsThe results showed that there were 40.78% caregivers experiencing caregiver burden. Patients who had a total dependence (PR 1.86; 95% CI 1021-3377), severe (PR 1.77; 95% CI 1026-3068), moderate (PR 2:08; 95% CI 1167-3710) and the duration of care for patients > 6 hours/day were significant factors affecting the caregiver burden on primary caregivers of stroke patients.ConclusionCaregivers burden is influenced by patient's condition and  care duration of patients. Education related to homecare for caregivers before patient was out from the hospital was needed as well as conducted regular consultations for the caregiver.